Classification and rippability of duricrusts - Mohd. Amin, Mohd. For (Faculty of Civil Engineering, UTM, 2005)
Strongly cemented or indurated sediments such as duricrusts exhibit certain properties that are similar to clastic sedimentary rocks. However, based on mode of formation, duricrusts cannot be classified as rock although their material properties bear a resemblance of rock. Consequently, excavation of this particular material in the field may lead to disputes between contractors and clients particularly pertaining to method of excavation and rate of payment for the excavation work. This paper discusses an initial study on duricrusts which emphasises on their mode of formation based on geological factors, and their material properties that are related to rippability. The initial study indicates that duricrusts can be classified according to their mode of formation and the types of cement matrix that are associated with their formation. In addition, duricrusts seem to exhibit similar properties as elastic sedimentary rocks consequently, ripping may be the suitable method for their excavation. A number of further assessments (laboratory and field tests) have been proposed for detailed verifications on the degree of rippability of these indurated sediments.